2019
DOI: 10.1002/gps.5113
|View full text |Cite
|
Sign up to set email alerts
|

The costs of dementia in England

Abstract: Objectives This study measures the average per person and annual total costs of dementia in England in 2015. Methods/Design Up‐to‐date data for England were drawn from multiple sources to identify prevalence of dementia by severity, patterns of health and social care service utilisation and their unit costs, levels of unpaid care and its economic impacts, and other costs of dementia. These data were used in a refined macrosimulation model to estimate annual per‐person and aggregate costs of dementia. Results T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 18 publications
(23 reference statements)
1
58
0
Order By: Relevance
“…In line with other evidence [1,2,6,41], we found that unpaid care costs of dementia were much higher than paid service costs, accounting for three-quarters of the total. Recent Table 5 Marginal means (95% CIs) (£) from two-part models of out-of-pocket, unpaid care time, and lost work time costs and GLM of total costs of paid and unpaid care cost-of-illness calculations [42] estimated that 42% of total costs of all individuals with dementia in England fell to unpaid care; another 25% were social care costs borne by individuals themselves. A recent systematic review [6] reported the share of total costs of dementia attributable to unpaid care as between 60% and 70%.…”
Section: Discussionmentioning
confidence: 99%
“…In line with other evidence [1,2,6,41], we found that unpaid care costs of dementia were much higher than paid service costs, accounting for three-quarters of the total. Recent Table 5 Marginal means (95% CIs) (£) from two-part models of out-of-pocket, unpaid care time, and lost work time costs and GLM of total costs of paid and unpaid care cost-of-illness calculations [42] estimated that 42% of total costs of all individuals with dementia in England fell to unpaid care; another 25% were social care costs borne by individuals themselves. A recent systematic review [6] reported the share of total costs of dementia attributable to unpaid care as between 60% and 70%.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies highlight the increase in resources needed by reporting the costs of formal medical and long-term care as a percent of Gross Domestic Product. In England, for example, it was estimated that the health and social care costs for people with dementia would rise from 0.8 percent of GDP in 2015 to 1.9 percent in 2040 (Wittenberg et al 2019).…”
Section: How Much Does Dementia Cost and How Much Will It Cost In Thmentioning
confidence: 99%
“…Supporting people with dementia is costly. Total cost in England in 2015 is estimated to be £24.2 billion, 16% of which was for health care, 42% social care, and 42% unpaid care by families and friends [8]. New projections to 2040 suggest that the number of older people in England with dementia will more than double by 2040 and costs more than treble in real terms [14].…”
Section: Contextmentioning
confidence: 99%
“…There are currently around 800,000 older people living with dementia in the UK and around 200,000 new cases of dementia annually [8]. AD accounts for around 72% of dementia cases when mixed dementia is included in the AD figures [9].…”
Section: Introductionmentioning
confidence: 99%